Legal Protection against Children of Criminal Acts of Narcotics Abuse Is Sent In Prison (Case Study Decision Number 12/Pid.Sus.anak/2017/PN Dps) - Warsifah Warsifah; Zulkarnain Arif (Budapest International Research and Critics University, 2022)
The phenomenon of juvenile delinquency in Indonesia is increasing, especially in terms of narcotics abuse which is an extraordinary crime, so that it is threatened with a fairly heavy crime. But on the other hand, perpetrators who are still children have the right to the principle of the best interests of children. So it can be said that the imposition of imprisonment on children does not provide a sense of protection to children, besides that children are victims of narcotics abuse as stipulated in Article 67 of Law no. 35 of 2014 concerning Child Protection. The problems in this study are (1) what is the judge's consideration in imposing a prison sentence on children who are perpetrators of narcotics crimes in Decision Number 12/Pid.Sus.Anak/2017/PN.Dps? seta (2) How is the provision of criminal sanctions in prison for children who are perpetrators of criminal acts of narcotics abuse according to the principles of juvenile criminal justice in Decision Number 12/Pid.Sus.Anak/2017/PN.Dps? This research is a normative juridical research so that what is studied are legal principles and legal rules that are still valid but are also supported by empirical data so that what is studied is data originating from the literature and court decisions. In imposing a prison sentence on a child who is a narcotics criminal in Decision Number 12/Pid.Sus.Anak/2017/PN.Dps, the judge is of the view that a child who is a drug abuser for himself is also a perpetrator of a crime/crime, so he must also still sentenced, therefore the judge's consideration in making a decision only affects the length of imprisonment, not a reason that affects the type of sanction given. Where the perpetrators who are still at the age of children are only used as mitigating things in terms of the length of imprisonment. Based on this, it can be seen that the child perpetrators of narcotics abusers in this case are still treated as mere criminals, regardless of the child as a victim. (2) The provision of imprisonment for children who are perpetrators of criminal acts of narcotics abuse according to the principle of juvenile criminal justice in Decision Number 12/Pid.Sus.Anak/2017/PN.Dps is deemed inappropriate, because the type of narcotic crime is included in a crime without victims. (crime without victim) which means that children as perpetrators here are victims, so that the imposition of criminal sanctions on children as narcotics abusers can have a negative impact on children in society such as dehumanization and stigmatization.